Neural Correlates of Physical Activity Moderate the Association Between Problematic Mobile Phone Use and Psychological Symptoms - Zou, Liwei; Wu, Xiaoyan; Tao, Shuman; Yang, Yajuan; Zhang, Qingjun; Hong, Xuedong; Xie, Yang; Li, Tingting; Zheng, Suisheng; Tao, Fangbiao (Frontiers in Behavioral Neuroscience, 2022)
Background: Despite evidence of an association between problematic mobile phone use (PMPU) and psychological symptoms, few studies explore whether physical activity (PA) could moderate the effect of PMPU on psychological symptoms and its neural substrates. The aim of current study is to examine the association between PMPU and psychological symptoms in late adolescents, along with the potential moderating effect of PA and neural basis by brain gray matter volume (GMV). Methods: A total of 251 college students reported on their PMPU, PA and psychological symptoms, and subsequently underwent structural magnetic resonance imaging to explore the neural basis of their PA characteristics. A multiple regression model was performed to detect brain GMV associated with PA by voxel-based morphometry (VBM) method. Moderating analysis was conducted using PROCESS macro in the SPSS software. Results: Behavioral results showed that, PMPU was correlated with depression, anxiety and stress, and PA has significantly moderated the association between PMPU with depression, anxiety and stress. The VBM analysis showed that PA was correlated with GMV of the right fusiform gyrus, the left precuneus, the left insula, and the left triangular part of inferior frontal gyrus. Moreover, GMV of left insula moderated the relationship between PMPU and depression. Conclusions: The present study shed light on the neural perspective of PA that moderate the relationship between PMPU and depressive symptom.